Insect attractants for enhanced monitoring and control of pests in rice storage - Balingbing, Carlito; Gummert, Martin; Pangesti, Nurmi; Van Hung, Nguyen; Hensel, Oliver (Elsevier, 2025)
Insect infestations in sub-optimal storage systems can lead to quantitative grain losses up to 85 %. The use of attractants can effectively monitor and control insect pests' populations in storage by capturing them in a trap and reducing insect density through elimination. This study focused on evaluating makeshift attractants to complement acoustic detection device for insects and as a means to monitor and control pests' infestations in grain storage. A Completely Randomized Design (CRD) experiment was set-up with three units of storage systems filled with rice paddy harvested at the International Rice Research Institute, Philippines to evaluate the effectiveness of attractants (red LED, air blower, vibration module and coconut oil, and a control) against storage insect pests (Rhyzopertha dominica, Sitophilus oryzae and Tribolium castaneum) in rice. The magnitude of the effect of attractant was determined by using the Cliff's Delta (Cliff's d) statistical measure for non-normally distributed data obtained in the experiment. Results showed that the red-light emitting diode (red LED) attracted R. dominica and S. oryzae in the three storage systems. The air blower attracted R. dominicaand T. castaneum. Insect density increased exponentially over a period of six months (R. dominica by 43x; S. oryzae by 18.6x; and T. castaneum by186x) effecting a negative correlation on the quality of milled rice recording a 2.9 % decrease in milling recovery and head rice yield by 2.9 % and 10.1 %, respectively, and increase in broken rice percentage by 27.3 %. The most effective attractants determined in this study will be used alongside an acoustic sensor for enhanced detection of pest insects that are normally dispersed in rice grain storage.